[Lord of Miracles sticker] - Rocco Murillo::::::photographer::: (2005)
Description supplied by photographer: "Una calcomanía de El Senor de Los Milagros en la puerta de mi casa en Paso Robles. Anuncia a todos que estamos orgullosos de ser originarios de San Juan Nuevo." Translation of description: "A sticker of the Lord of Miracles on the front door of my house in Paso Robles. The sticker tells other people that we are proud of where we come from."